2011
DOI: 10.1007/s13595-011-0085-z
|View full text |Cite
|
Sign up to set email alerts
|

The decreasing radial wood stiffness pattern of some tropical trees growing in the primary forest is reversed and increases when they are grown in a plantation

Abstract: Background This study examines the radial trend in wood stiffness of tropical rainforest trees. The objective was to determine if the type of growing environment (exposed plantation or dense primary forest) would have an effect on this radial trend. Methods The axial elastic modulus of wood samples, representing a pith to bark cross-section, of six trees from several French Guianese species (two of Eperua falcata, one of Eperua grandiflora, two of Carapa procera and one of Symphonia gloubulifera) was me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…The juvenile wood formed in the control trees under these conditions had values of density, MOE and MOR similar to those of the mature wood (Table 2), whereas density and MOE of the juvenile wood of the re-spaced trees were inferior to those of the mature wood. McLean et al (2011) observed a broadly similar effect in a study on the wood properties of several naturally regenerated tropical species from primary forest and the same species growing under more widely spaced plantation conditions. Given that grain angle was too low in both treatments to significantly influence strength (e.g.…”
Section: Discussionmentioning
confidence: 63%
“…The juvenile wood formed in the control trees under these conditions had values of density, MOE and MOR similar to those of the mature wood (Table 2), whereas density and MOE of the juvenile wood of the re-spaced trees were inferior to those of the mature wood. McLean et al (2011) observed a broadly similar effect in a study on the wood properties of several naturally regenerated tropical species from primary forest and the same species growing under more widely spaced plantation conditions. Given that grain angle was too low in both treatments to significantly influence strength (e.g.…”
Section: Discussionmentioning
confidence: 63%
“…Zobel and Sprague 1998;Woodcock and Shier 2002;Lachenbruch et al 2011;Plourde et al 2015) and typical radial patterns (TRP) of variations of functional or material properties of wood have been reported (Lachenbruch et al 2011). However, some radial trends may be strongly modified by changing growth conditions for the same species (McLean et al 2011).…”
Section: Introductionmentioning
confidence: 98%
“…This differs from most tree species but is consistent with the mechanical strategy among climbing plants [17], [73], where early juvenile stages of growth are nearly always optimised for stiff “searching” behaviour and older stages of growth are comprised of more flexible material, once the plant has attached to its support. A recent study has also found a decrease in stiffness from the inside to outside of the stem in tropical tree species grown in closed forest conditions [74], implying that MFA can change in response to open or closed environmental conditions in tree species.…”
Section: Discussionmentioning
confidence: 93%